Coronary heart disease prevention: insights from modelling incremental cost effectiveness - Marshall, Tom (BMJ Group, 2003)
Objective To determine which treatments for preventing coronary heart disease should be offered to which patients by assessing their incremental cost effectiveness. Design Modelling study Data sources Cost estimates (for NHS) and estimates of effectiveness obtained for aspirin, antihypertensive drugs, statins and clopidogrel. Data synthesis Treatment effects were assumed to be independent, and cost per coronary event prevented was calculated for treatments individually and in combination across patients at a range of coronary risks. Results The most cost effective preventive treatments are aspirin, initial antihypertensive treatment (bendrofluazide and atenolol), and intensive antihypertensive treatment (bendrofluazide, atenolol and enalapril), whereas simvastatin and clopidogrel are the least cost effective (cost per coronary event prevented in a patient at 10% coronary risk over five years is £3500 for aspirin, £12 500 for initial antihypertensives, £18 300 for intensive antihypertensives, £60 000 for clopidogrel, and £61 400 for simvastatin). Aspirin in a patient at 5% five year coronary risk costs less than a fifth as much per event prevented (£7900) as simvastatin in a patient at 30% five year risk (£40 800). Discussion A cost effective prevention strategy would offer aspirin and initial antihypertensive treatment to all patients at greater than 7.5% five year coronary risk before offering statins or clopidogrel to patients at greater than 15% five year coronary risk. Incremental cost effectiveness analysis of treatments produces robust, practical cost effectiveness rankings that can be used to inform treatment guidelines.